Numerical simulation analysis and optimum design for combined type pressure reducing valves. Issue 1 (May 2016) - Gou, D M; Guo, P C; Zheng, X B; Luo, X Q; Sun, L G
Abstract: Pressure reducing valve is an extremely significant equipment of energy dissipation for the water supply by gravity with pressure reducing technology in hydropower stations, and which has a pronounced effect on the normal technical water supply even safety operation for the hydropower units. A three-dimensional numerical calculation of flow field and cavitation characteristics towards a combined type pressure reducing valves was carried out based on the system of technical water supply in this paper. The numerical results show that the investigated valve could meet the requirements of technological supply water pressure and great pressure loss was caused when the water flow was accelerated by narrow overflowing section between throttling cone and valve seat. At working operation, obvious cavitation phenomenon was observed on the surface of throttling cone, and the maximum volume fraction of vapor reached 0.537%. Based on above researches, this paper introduces an optimization model for profile line design of throttling cone. The optimal results show that the cavitation performance is effectively improved with identical pressure drop compared with original results.